(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article describes the legal aspects of the state policy of the Republic of Uzbekistan on the regulation of interethnic relations in the country. In particular, a number of articles of the Constitution of the Republic of Uzbekistan regarding the provision of rights and freedoms of representatives of different nationalities and peoples living in the country were touched upon. Also, attention is paid to the laws and legislative documents adopted in this direction.